Penilaian Perkembangan Tanah Berdasarkan Tingkat Pencucian Liat Dan Nilai Kapasitas Tukar Kation Pada Daerah Hulu Sungai Sangatta Kutai Timur - Norrahmad, Norrahmad; Edwin, Muli; Putra, Mufti Perwira (Sekolah Tinggi Pertanian Kutai Timur, 2015)
The purpose of this study is to see the extent of the development of clay soil by leaching and the value of Cation Exchange Capacity (CEC) at study sites in the upstream areas Sangatta. Soil is a natural body at the earth's surface formed by the influence of factors of soil formation. In the process of soil formation factors are interrelated or some may be dominant factors that influence the formation of heterogeneous land surface of the earth. The level of development of the land had been developed further ground if kandugan minerals are easily weathered primary is less than difficult weathered minerals. Furthermore, for a description of the condition of the soil and the soil profile observation pengampilan soil samples for laboratory analysis. From the results of calculations and laboratory analysis will be described in quantitative descriptive presented in tabels and graphs. At the study site is a plateau or hilly slope which has 28% with altitude of about 100 m asl. From the research, the development of land at the study site is influenced by several factors, especially soil formation factors tofografi ie slope and altitude, and climatic factors (rainfall). Based on the rate of leaching of clay, soil development on the location of the study prove the land is still in the early stages of development level. Such soil clay content which generally have little and no addition of clay seiiring with increasing soil depth. Then further evidenced by clay CEC value is 35,06 meq/100 indicating that land is the land with the development of the initial level or younger soil. Both based on the level of leaching and clay CEC and clay mineral content of the soil is known Illit most likely a young land, ie the order Alluvial soil (PPT Bogor) or Entisol (USDA).